Gymnemic acid content in Gymnema Sylvestre accessions collected from different regions of India (Open Access Journal of Medicinal and Aromatic Plants, 2011)
(Abstract selected from presentation in National Conference on Biodiversity of Medicinal and Aromatic Plants: Collection, Characterization and Utilization, held at Anand, India during November 24-25, 2010) Â Gymnemic acid, a triterpenoid saponin, is the important active compound of Gymnema Sylvestre, known for its anti-diabetic activity. Thirty seven plant samples collected from different locations across India (Andhra Pradesh, Gujarat, Karnataka, Kerala, Madhya Pradesh, Tamil Nadu and Uttar Pradesh) were analysed for the gymnemic acid content by HPTLC method. Gymnemic acid occurs in plants in a group of oleananetype triterpenoid saponins (gymnemic acid I-IX) and it was estimated through estimating gymnemagenin (aglycon of gymnemic acid). Leaf powder was hydrolysed in alcoholic medium by refluxing on boiling water bath and neutralised. It was further extracted by ethyl acetate three times and concentrated to known volume. Sample was applied on TLC Silica gel 60 F254 plate along with Gymnemagenin standard and developed in mobile phase mixture of chloroform and methanol in ratio of 8:2. Plates were derivatised by 5% H2SO4 and scanned at 366 nm. Gymnemic acid content in the samples ranged from 0.28% to 2.06% in the accessions. Highest gymnemic acid content was found in the accession DGS 2, which was collected from the Dangs forests and trace level (below detection level) was recorded in six accessions collected from Kerala (DGS 24, DGS 25), Karnataka (DGS 10, DGS 13 and DGS 14) and Andhra Pradesh (DGS 19). It was found that the gymnemic acid content in accessions was influenced by genotypic and ecogeographical conditions. Further investigations are needed to understand the mechanism of genotype and environmental interactions affecting gymnemic acid accumulation.